(untitled) (Semiárida, 2020)
The fluvic acid fraction in considered to be sensitive to agronomic and environment factors. Therefore, the objectives of this study were to evaluate total carbon (TC) and fluvic acid carbon (FC) contens and to establish a possible relationship between the FC fraction and coarse organic matter in agricultural soils (CTVs), (ii) conservation tilled soils (CSTs), and (iii) virgins soils (VIRs) from a wide region in Argentina. The investigation includes 114 surface samples of Hapludolls, Haplustolls, and Entisols ranging in texture from sand to slit loam. In 29 selected samples, two separate soil mineral fraction were used (<0.05 mm and 0.1-2 mm) to determinate FC and TC contents. No statistically significant differences were found in TC contents in the fine fraction < 0.05 mm between VlRs, CSTs, and CVTs; however, FC contents were higher in VIRs than in CSTs and CVTs at the 0.05 probability level. In addition" statistically significant differences (P< 0.05) observed in FC contents among all three treatments in the coarse fraction 0.1-2 mm confirm that the FC fraction Is more influenced by the farming-system thn Is TC. Moreover, FC I TC ratios tended to increase under agricultural land use (CVTs > CSTs > VIRs), and this radio also Increased from finer textured soils to creaser tent was highly related to recently incorporated organic residues. Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Publicado en Soil Science 1999; Vol 164: 57-61